Pelatihan Pengelolaan Teaching Factory (TeFa) di SMK Muhammadiyah Purwodadi - Aci Primartadi; Dwi Jatmoko; Arif Susanto; Ady Prasetyo Utomo; Rivan Dwi Haryanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the quality of vocational education by strengthening the management of the Teaching Factory (TeFa) at SMK Muhammadiyah Purwodadi. This model requires active student involvement in the production of goods or services in accordance with workplace standards, thereby fostering technical, managerial, and professional competencies. The implementation method uses a participatory and collaborative approach, encompassing four main stages: (1) identifying the needs and readiness of target schools, (2) developing training materials based on the results of the needs analysis, (3) implementing TeFa management training using a problem-solving approach and hands-on practice, and (4) providing post-training mentoring and evaluation. The results of the activity demonstrated a significant improvement in the managerial and technical capabilities of TeFa managers. Based on the evaluation results, participants were able to develop a production management plan integrated with the curriculum. In addition, training participants successfully implemented the concept of industrial cooperation in learning activities. Positive impacts were also seen from the increase in student participation in production projects and the increasing variety of workshop service products managed by the School. Thus, this training model can be used as a reference for other vocational schools in developing productive, innovative, and competitive TeFa management.